(untitled) (International Journal of Engineering and Computer Science, 2015)
The Wireless Sensor Networks (WSNs) have become popular with the increasing development of the smart sensors. Since the sensors used in these networks, operate on the limited battery capacity so that energy efficiency is the main goal. Energy efficiency of MAC protocols is one the wide research area because a major energy consuming component of sensor called as radio, is controlled by MAC protocols. In this paper a protocol known as Cluster Based SMAC (CBSMAC) protocol has been proposed which is based on SMAC protocol and the results has been further analyzed by using ns2 tool to show that CBSMAC is more energy efficient in comparison to SMAC